The Hepatoselective Glucokinase Activator PF-04991532 Ameliorates Hyperglycemia without Causing Hepatic Steatosis in Diabetic Rats - Erion, Derek M.; Lapworth, Amanda; Amor, Paul A.; Bai, Guoyun; Vera, Nicholas B.; Clark, Ronald W.; Yan, Qingyun; Zhu, Yimin; Ross, Trenton T.; Purkal, Julie; Gorgoglione, Matthew; Zhang, Guodong; et al. (PLOS ONE, 2014)
Hyperglycemia resulting from type 2 diabetes mellitus (T2DM) is the main cause of diabetic complications such as retinopathy and neuropathy. A reduction in hyperglycemia has been shown to prevent these associated complications supporting the importance of glucose control. Glucokinase converts glucose to glucose-6-phosphate and determines glucose flux into the β-cells and hepatocytes. Since activation of glucokinase in β-cells is associated with increased risk of hypoglycemia, we hypothesized that selectively activating hepatic glucokinase would reduce fasting and postprandial glucose with minimal risk of hypoglycemia. Previous studies have shown that hepatic glucokinase overexpression is able to restore glucose homeostasis in diabetic models; however, these overexpression experiments have also revealed that excessive increases in hepatic glucokinase activity may also cause hepatosteatosis. Herein we sought to evaluate whether liver specific pharmacological activation of hepatic glucokinase is an effective strategy to reduce hyperglycemia without causing adverse hepatic lipids changes. To test this hypothesis, we evaluated a hepatoselective glucokinase activator, PF-04991532, in Goto-Kakizaki rats. In these studies, PF-04991532 reduced plasma glucose concentrations independent of changes in insulin concentrations in a dose-dependent manner both acutely and after 28 days of sub-chronic treatment. During a hyperglycemic clamp in Goto-Kakizaki rats, the glucose infusion rate was increased approximately 5-fold with PF-04991532. This increase in glucose infusion can be partially attributed to the 60% reduction in endogenous glucose production. While PF-04991532 induced dose-dependent increases in plasma triglyceride concentrations it had no effect on hepatic triglyceride concentrations in Goto-Kakizaki rats. Interestingly, PF-04991532 decreased intracellular AMP concentrations and increased hepatic futile cycling. These data suggest that hepatoselective glucokinase activation may offer glycemic control without inducing hepatic steatosis supporting the evaluation of tissue specific activators in clinical trials.